A study on relationship between communication models and crisis management in Tehran’s firefighting department - Saeed Emamqoli Zade; Amir Nasserian; Ali Akbar Aghaei (Management Science Letters)
This research presents an empirical investigation to study the relationship between communication models and crisis management in city of Tehran municipal firefighting department. The study develops a questionnaire with 21 questions, distributes it among 400 people who worked for firefighting department associated with municipality of Tehran, Iran. Crobnach alphas for all components of the survey were well above the minimum acceptable level of 0.7. Kolmogorov–Smirnov test has indicated that all components of the survey were normally distributed. Using a t-student test, the study determined that there were meaningful relationships between communication models and crisis management (sig: 0.000), between vertical model and crisis management (sig: 0.000), between ring model and crisis management (sig: 0.000), between star model and crisis management (sig: 0.000) and between Y model and crisis management (sig: 0.000) in Tehran municipal fire department.